PENGARUH PEMBERIAN EKSTRAK KACANG HIJAU (Vigna radiata) TERHADAP KUALITAS NATA DE CASSAVA DARI LIMBAH KULIT SINGKONG SEBAGAI RANCANGAN POSTER MATERI BIOTEKNOLOGI DI SMA - Wahyuningsih, Sri; Darmawati, Darmawati; Fauziah, Yuslim (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research was conducted to determine the effect of mung bean extract on the quality of Nata de cassava and poster design of biotechnology subject matter at the XII grade high school level in June-August 2020. This research was conducted in 2 stages, namely the experimental stage: the effect of giving mung bean extract to the quality of Nata de Cassava and the second stage of poster design: analysis of the potential development of biotechnology teaching materials for class XII high school level. This study used an experimental method by conducting experiments at the Laboratory of the Faculty of Mathematics and Natural Sciences (FMIPA), Pekanbaru. Sampling was carried out with a completely randomized design (CRD) consisting of 4 treatments and 3 replications. The parameters in this study were thickness analysis and acidity (pH) analysis. Based on the results of the Analysis of Variance (ANOVA) at the 5% level, giving green bean extract showed a significant effect on the quality of Nata de cassava. Giving green bean extract of 600 ml gives an increase in the quality of the best Nata de cassava and based on the analysis of the potential research results can be used as a poster design for class XII high school level biotechnology material.Key Words: Quality Nata de Cassava, Poster design, Mung bean extract